(untitled) (Advances in Oceanography and Limnology, 2013)
Stakeholder participation has received increased attention as a key process for enhancing mitigation of conflicts between different interests for the same resources and transparent decision-making in marine protected areas (MPAs). A wide range of advanced web tools is available nowadays that integrate stakeholder participation by generating new information and allow interaction between actors in MPA management. However, such technologies are frequently used without much consideration regarding the complexity of the decision to be made and the heterogeneity of stakeholder preferences and understanding in order to be related to these technologies. In order to understand how technology corresponds to the changing needs of MPA management, we have reviewed a range of different participation strategies adopted by web technology, based on a set of criteria that define a successful participation approach. We start from simple towards more sophisticated tools that have been developed worldwide in order to better inform decisions, and contribute to more effective and efficient MPA management. Finally, we draw a theoretical framework for the development of a community-based web tool with the capacity to incorporate the philosophy of stakeholder participation by generating new and high quality information flow for effective MPA management.